2010
DOI: 10.1007/s11195-010-9189-x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Sexual Relationships Between Elderly People Residing in Nursing Homes

Abstract: The overall level of acceptability expressed by French people aged 18-84 years regarding sexual relationships among elderly persons was examined as well as the effect on acceptability of four factors: partners' age, marital status, duration of the relationship, and privacy. Four hundred and twenty seven participants were presented with 36 vignettes of a few lines that were composed according to a four within-subject factor design. A cluster analysis revealed three basic philosophies regarding acceptability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although increasing age does not directly preclude sexual desire (Esterle, Sastre, & Mullet, 2011; Kontula & Haavio-Mannila, 2009), it is reported to be a statistical predictor of sexual inactivity among older, married adults (Karraker & DeLamater, 2013). Additional research has shown that the frequency and type of sexual behavior changes as people age across the life span (Elias & Ryan, 2011; Ginsberg, Pomerantz, & Kramer-Feeley, 2005; Katz, 2013).…”
Section: Age Of the Residentmentioning
confidence: 99%
“…Although increasing age does not directly preclude sexual desire (Esterle, Sastre, & Mullet, 2011; Kontula & Haavio-Mannila, 2009), it is reported to be a statistical predictor of sexual inactivity among older, married adults (Karraker & DeLamater, 2013). Additional research has shown that the frequency and type of sexual behavior changes as people age across the life span (Elias & Ryan, 2011; Ginsberg, Pomerantz, & Kramer-Feeley, 2005; Katz, 2013).…”
Section: Age Of the Residentmentioning
confidence: 99%
“…In view of these findings, we expected to find at least three different philosophies regarding the acceptability of sexual relationship among PLD: (a) an ''always acceptable'' philosophy, comparable to the one found in Esterle et al [20] study, (b) a ''never acceptable'' philosophy, that should reflect the viewpoint of Mexican people who are older and/or more religiously oriented, and (c) a ''depending on circumstances'' philosophy that should reflect the viewpoint of the majority of the participants, as in the study by Morales et al [12]. In the subsample of family caregivers, 25 of them were parents of PLD suffering from Down syndrome and 50 of them were parents of PLD suffering from a neuromotor disorder.…”
Section: The Present Studymentioning
confidence: 63%
“…Using a Q-sort technique, they distinguished four different philosophies: advocates of sex education, supporters of sex education, regulators and humanists. Esterle, Munoz Sastre and Mullet [20] in a study about elderly people's sexuality, showed that three qualitatively different philosophies coexisted among lay people.…”
Section: The Present Studymentioning
confidence: 99%
“…Sexuality is a fundamental component of life from birth until death, and healthy intimate relationships are essential to overall well-being throughout the life span (Esterle, Sastre, & Mullet, 2011; Sumter, Valkenburg, & Peter, 2013; Thompson et al, 2011; Zeiss & Kasl-Godley, 2001). Although the frequency of sexual behavior declines with age (DeLamater & Moorman, 2007), the intrinsic desire for meaningful intimate relationships remains and is not thwarted by admission to a long-term care (LTC) facility (Di Napoli, Breland, & Allen, 2013; Elias & Ryan, 2011; Katz, 2013; Reingold & Burros, 2004).…”
mentioning
confidence: 99%